2019
DOI: 10.1136/vr.105291
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of ovine mortality in sentinel sheep flocks in Ireland

Abstract: BackgroundStudies of sheep mortality or cause-specific mortality, in Ireland or internationally, are relatively scarce but are important in presenting baseline levels and changing trends of endemic disease. This study assessed sheep mortality and cause-specific mortality in 33 sentinel sheep flocks in Ireland.MethodsSentinel flocks were requested to submit carcases of all sheep that died to the regional veterinary laboratories (RVLs) of the Department of Agriculture, Food and Marine during a calendar year (201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
(48 reference statements)
2
18
0
1
Order By: Relevance
“…However, disease investigations reported in this study were derived from submissions by veterinarians to animal health laboratories, which rely on farmers identifying abortion in the flock, reporting this to veterinarians, suitable samples being available for submission to the laboratory and veterinarians making the decision to submit samples for testing. This is associated with the potential for bias and the risk of over‐ or underreporting specific diseases 34 . Therefore, the incidence of abortion in Australian sheep or the true incidence of specific diseases cannot be derived from data included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, disease investigations reported in this study were derived from submissions by veterinarians to animal health laboratories, which rely on farmers identifying abortion in the flock, reporting this to veterinarians, suitable samples being available for submission to the laboratory and veterinarians making the decision to submit samples for testing. This is associated with the potential for bias and the risk of over‐ or underreporting specific diseases 34 . Therefore, the incidence of abortion in Australian sheep or the true incidence of specific diseases cannot be derived from data included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…'No diagnosis' was recorded for approximately 5 per cent of carcases in every age group, except for fetuses -where a cause of death could not be identiied for two-thirds of the submitted carcases. 12 For most veterinary practitioners with a caseload involving sheep locks, there will be no great diferences between the conditions found in this study and their own ield observations, with the majority of carcase submissions being made around the lambing period (February to April). Where there are diferences, it will be worthwhile to relect on why that may be the case.…”
mentioning
confidence: 55%
“…11 In a paper summarised on p 649 of this issue of Vet Record, Murray and colleagues describe the results of a year-long sentinel surveillance study of mortality and its causes in 33 Irish lowland sheep locks. 12 The study provides baseline estimates of the frequency of mortality and cause-speciic mortality in four ovine age groups (fetus, perinate, lamb and adult), as determined by a standardised detailed postmortem examination. It also provides estimates of the seroprevalence of seven infectious agents that can cause abortion, and of farmerreported use of relevant vaccinations.…”
mentioning
confidence: 99%
“…Surveillance data, however, suggest a likely low prevalence. Murray et al, [15] notes anecdotal suggestions that a small number of flocks in Ireland are experiencing significant within-flock prevalence of laryngeal chondritis. Surprisingly, a high percentage (81.5%) of those surveyed in the current study indicated they previously have had sheep in their flock with 'throat problems'.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of sentinel flocks in Ireland, Murray et al [15] indicated the specific requirement for further research investigating laryngeal chondritis in Irish flocks.…”
Section: Introductionmentioning
confidence: 99%